Identifying Farming Strategies Associated With Achieving Global Agricultural Sustainability - Smith, Olivia M.; Jocson, Dowen M. I.; Lee, Benjamin W.; Orpet, Robert J.; Taylor, Joseph M.; Davis, Alexandra G.; Rieser, Cassandra J.; Clarke, Abigail E.; Cohen, Abigail L.; Hayes, Abigail M.; Auth, Connor A.; Bergeron, Paul E.; et al. (Frontiers in Sustainable Food Systems, 2022)
Sustainable agroecosystems provide adequate food while supporting environmental and human wellbeing and are a key part of the United Nations Sustainable Development Goals (SDGs). Some strategies to promote sustainability include reducing inputs, substituting conventional crops with genetically modified (GM) alternatives, and using organic production. Here, we leveraged global databases covering 121 countries to determine which farming strategies – the amount of inputs per area (fertilizers, pesticides, and irrigation), GM crops, and percent agriculture in organic production – are most correlated with 12 sustainability metrics recognized by the United Nations Food and Agriculture Organization. Using quantile regression, we found that countries with higher Human Development Indices (including education, income, and lifespan), higher income equality, lower food insecurity, and higher cereal yields had the most organic production and inputs. However, input-intensive strategies were associated with greater agricultural greenhouse gas emissions. In contrast, countries with more GM crops were least on track to meeting the SDG of reduced inequalities. Using a longitudinal analysis spanning 2004–2018, we found that countries were generally decreasing inputs and increasing their share of agriculture in organic production. Also, in disentangling correlation vs causation, we hypothesize that country development is more likely to drive changes in agricultural strategies than vice versa. Altogether, our correlative analyses suggest that countries with greater progress towards the SDGs of no poverty, zero hunger, good health and wellbeing, quality education, decent work and economic growth, and reduced inequalities had the highest production of organic agriculture and, to a lesser extent, intensive use of inputs.